How not to make a human : pets, feral children, worms, sky burial, oysters - Steel, Karl (University of Minnesota Press, 2019)
"How Not to Make a Human seeks to provide a posthuman and ecocritical interrogation of human particularity via a wide range of medieval texts. Exploring such diverse topics as medieval pet-keeping, stories of feral and isolated children, interest in the edibility of the human body, sky burials, Chaucer, and oysters, from a variety of disanthropic perspectives, Steel furnishes contemporary posthumanists with underutilized cultural models in which humans play a humbler part than they have tended to in the last several centuries"--